Political Engagement and Crime Victimization: A Causal Analysis - Laterzo, Isabel (Revista Latinoamericana de Opinión Pública, 2021)
In recent years, research has demonstrated that crime victimization serves as a catalyst to political engagement. However, much of this work has not addressed two key issues: 1) the true causality of this relationship, and 2) how victims’ identities and personal experiences might influence this relationship. This paper tackles these issues by testing the effect of victimization on non-electoral engagement using the Two-City, Six-Wave panel survey administered in Brazil between 2002 and 2006. It finds that the causal relationship between victimization and engagement only exists for participation in political party meetings. Furthermore, when exploring the role of individual identity and community context, only men, those who live in safe neighborhoods, and White Brazilians experience an increase in their engagement. Meanwhile, women, those in unsafe neighborhoods, and Afro-Brazilians do not experience such an increase. Those who have not experienced discrimination also increase their participation, while those who have experienced discrimination do not.